(untitled) (Scientific journal of the Fergana State University, 2024)
The article talks about the interpretation of the era and the hero in Uzbek and German dramas of the 20th century. Based on artistic analysis, poetic methods that shed light on the era and character of the hero were researched. The 20th century was a special transitional period in the German dramaturgy, which was influenced by the Uzbek dramaturgy of the 60s-90s and the currents of naturalism and critical realism. Any transitional period, issues of man and his role in society become an important problem that needs to be solved. The influence of the national literature of each nation is reflected in its contribution to the treasury of world literature, and in comparison with other literatures. In particular, to see similarities and unique aspects between the Uzbek dramaturgy of the 60s-90s of the 20th century and the German dramaturgy of the beginning of the 20th century, which focused on reflecting various modern themes in our country. possible There were serious changes in the cultural, political, and social life of both regions, as well as a sharp ideological struggle.